2021
DOI: 10.23822/eurannaci.1764-1489.168
|View full text |Cite
|
Sign up to set email alerts
|

Immune signature of CCR7+ central memory T cells associates with disease severity and Immunoglobulin E in bronchial asthma

Abstract: Objectives: CD4+T cell subtypes are the central orchestrators of airway inflammation in bronchial asthma (BA); however, the mechanisms that regulate their accumulation in asthmatic airways are still a challenging subject. In addition, neutrophils play a significant role in the development of airway remodeling and their presence may influence clinical presentation of BA being linked to the development of severe BA. Neutrophils have also been found to acquire antigen presenting functions, enabling them to direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
7
0
2
Order By: Relevance
“…There was no difference in the cell numbers of T CM and T EM among the groups. It has been reported that the immune characteristics of CCR7 + T CM were significantly correlated with asthma severity and IgE levels, and the proportion of CCR7 + T CM in peripheral blood mononuclear cells (PBMC) in patients with allergic asthma was significantly higher than that in patients without allergic asthma (22). However, the airway immune microenvironment of asthma is complex and ample experimental evidence supports that T CM and T EM cells can be converted to the other cell type in many conditions (21,23), hence, the exact mutual proportion of T CM and T EM need to be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no difference in the cell numbers of T CM and T EM among the groups. It has been reported that the immune characteristics of CCR7 + T CM were significantly correlated with asthma severity and IgE levels, and the proportion of CCR7 + T CM in peripheral blood mononuclear cells (PBMC) in patients with allergic asthma was significantly higher than that in patients without allergic asthma (22). However, the airway immune microenvironment of asthma is complex and ample experimental evidence supports that T CM and T EM cells can be converted to the other cell type in many conditions (21,23), hence, the exact mutual proportion of T CM and T EM need to be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Allergen-specific Th2 memory cells have been viewed as fundamental for the development of allergic asthma in both human and animal models ( 22 ), and DC regulate the generation of memory T cells at each stage via the interplay between these cells ( 38 ). T CM has the characteristics of self-renewal ability and long-term memory, which can proliferate after antigen restimulation; while the proliferation ability of T EM is lower than T CM , whose function is similar to effector T cell ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of these control mechanisms is the ability to inhibit the differentiation of T CM . Yet, a recent report showed that in severe asthma patients, the percentage of CCR7 high memory T cells in the blood was signi cantly lower than in the control group; thus, the distribution between lung, blood and peripheral lymphatic organs may be disordered in severe asthma [29]. Previous research has described that AST had an anti-in ammatory effect and could prevent the recurrence of asthma [30].…”
Section: Discussionmentioning
confidence: 98%
“…Central memory T cells enter into secondary lymphoid organs, proliferate, and produce a higher percentage of effector memory phenotype cells, which are to the acute in ammation in lung tissues [27]. A recent report also revealed that increased CCR7 high central memory T cells were associated with asthma severity [28]. of these control mechanisms is the ability to inhibit the differentiation of T CM .…”
Section: Discussionmentioning
confidence: 99%